Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1183/13993003.00209-2016
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study characterising a large adult primary ciliary dyskinesia population

Abstract: Primary ciliary dyskinesia (PCD) in adults has not been well described. In this retrospective observational study we aimed to characterise a large adult population and identify features associated with disease progression.We retrospectively analysed 151 adult patients at a single tertiary centre at baseline and longitudinally for a median of 7 years.We found significant variation in age at diagnosis (median 23.5 years; range <1-72 years). Older age at diagnosis was associated with impaired baseline forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(139 citation statements)
references
References 32 publications
13
122
2
2
Order By: Relevance
“…Despite counterintuitive, the lack of association between early PCD diagnosis and better pulmonary outcomes, strongly suggested by our results, has been highlighted previously [31, 32]. Furthermore, a recent longitudinal study of adult PCD subjects has confirmed that, even though negatively associated with baseline FEV 1 , age at diagnosis does not correlate with longitudinal functional measurements, thus raising doubts on the real impact of optimal management at an early stage on the subsequent disease progression [33]. These studies did not correlate chest CT scores with age at diagnosis, but it is reasonable to hypothesize that, likewise functional impairment, also structural abnormalities are poorly affected by it.…”
Section: Discussionsupporting
confidence: 40%
“…Despite counterintuitive, the lack of association between early PCD diagnosis and better pulmonary outcomes, strongly suggested by our results, has been highlighted previously [31, 32]. Furthermore, a recent longitudinal study of adult PCD subjects has confirmed that, even though negatively associated with baseline FEV 1 , age at diagnosis does not correlate with longitudinal functional measurements, thus raising doubts on the real impact of optimal management at an early stage on the subsequent disease progression [33]. These studies did not correlate chest CT scores with age at diagnosis, but it is reasonable to hypothesize that, likewise functional impairment, also structural abnormalities are poorly affected by it.…”
Section: Discussionsupporting
confidence: 40%
“…Information on PCD disease progression is still incomplete, even though the mortality data are hard to interpret, as they are not age standardized. A recent retrospective study of 151 PCD adults with a median age of 35 years longitudinally followed for 7 years found an incidence of all-cause mortality of nearly 5%, and a respiratory mortality of 3.3% (62). Authors showed that older age at diagnosis was associated with impaired baseline FEV 1 and increased P. aeruginosa colonization.…”
Section: Disease Manifestationsmentioning
confidence: 99%
“…Models of transitional care for cystic fibrosis might inform PCD care; the need for collaborative working between paediatric and adult clinics is essential to enable longitudinal understanding of the patient "from cradle to grave". The article by SHAH et al [1], although describing a population that originated from the paediatric service in the same hospital, does not draw on health status in childhood. The earliest information presented in the article dates from the time of transfer to adult services.…”
Section: Transition From Paediatric To Adult Carementioning
confidence: 99%
“…The North American Disorders of Mucociliary Clearance Consortium reported half of the patients initially labelled as "PCD" were de-diagnosed after extensive testing [31]; conversely, we are aware of patients whose investigations had previously "excluded a diagnosis" where that decision has been overturned. In the study described by SHAH et al [1], nNO had been measured in only two-thirds of the patients (64%), although it is a noninvasive and affordable test.…”
Section: Do "Older Patients" Profit From New Developments?mentioning
confidence: 99%
See 1 more Smart Citation